Echocardiographic assessment of left ventricular function in coronary arterial disease. Issue 2 (February 1977) - Chandraratna, P A; Rashid, A; Tolentino, A; Hildner, F J; Fester, A; Samet, P; Littman, B B; Sabharwal, S
Abstract : This investigation was designed to determine the role of echocardiography in the assessment of left ventricular function in patients with significant coronary arterial disease. Satisfactory echocardiograms were obtained in 43 patients with coronary arterial disease. The ventriculographic ejection fraction was determined by the area length method. The echocardiographic left ventricular end-diastolic dimension was increased to more than 5-4 cm in 17 patients. Fifteen of these patients had an ejection fraction of 0-45 or less. Three patients had a normal left ventricular end-diastolic dimension but an ejection fraction of less than 0-45. Twenty-three patients had an ejection fraction of more than 0-45 and a normal left ventricular end-diastolic dimension. The left ventricular end-diastolic dimension index was increased (greater than 3 cm/m2) in 15 patients, all of whom had ejection fraction of less than 0-45. Three patients had a normal left ventricular end-diastolic dimension index and an ejection fraction of less than 0-45. Twenty-five patients had a left ventricular end-diastolic dimension index of less than 3 cm/m2 or less and an ejection fraction of more than 0-45. The percentage fractional shortening of the echocardiographic left ventricular dimension was reduced in 25 patients. In 18 of these the ejection fraction was 0-45 or less. The percentage fractional shortening of the left ventricle was normal in 18 patients. In 2 of them the ejection fraction was less than 0-45. In summary, increase of the left ventricular end-diastolic dimension or left ventricular end-diastolic dimension index is usually associated with a critical reduction of the ejection fraction as determined by ventriculography. Since the ejection fraction is an important determinant of mortality related to bypass graft surgery, echocardiography should be useful in the detection of patients with a poor prognosis.